Determinan kepuasan pengguna aplikasi SAIBA pada satker mitra kerja KPPN Pekanbaru dengan kualitas SDM sebagai variabel intervening - Edinov, Sally; Indrawati, Novita; Taufik, Taufeni; Basri, Yesi Mutia; Nur D, Emrinaldi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study is for the impact of the effects of system quality, information quality, quality, quality, quality, quality, service quality, and human resource quality on Saiba application user satisfaction and the impact of quality, information and service quality. It is. Saiba Application Satisfaction Quality HR Quality This research was conducted for Pekanbaru KPPN partners, including 66 respondents from 66 tourist objects. Similar to collecting data with questionnaires, the sensuous technique is sampled. The survey results from the data analysis technology survey were completed using multiple regression analysis and multiple regression analysis (MRA) through the SPSS application: (1) system quality, information quality, quality, quality of natural resources, Saiba user satisfaction has a severe impact. (2) HR quality can strengthen the system quality relationship across the Saiba application satisfaction. (3) The quality of human resources can strengthen the relationship between the quality and the quality of human resources with the satisfaction of users of the Saiba application. (4) The quality of human resources can strengthen the relationship with users' satisfaction with the Saiba application through the quality of the Human Resources of the Pekanbaru-KPPN Satker.